Model tests of soil heave plug formation in suction caisson - Guo, Wei (2018)
An experimental study of the formation of the soil heave plug inside a concrete caisson during installation in clay under suction is presented. The soil heave plug, the amount of caisson penetration and the vacuum pressure applied were measured during the model tests. The results show that the soil heave plug can completely fill in the cavity and prevent the caisson from penetrating further. The soil heave plug is affected by the geometry of the caisson. The higher the consolidation stress or the stiffer the soils, the higher is the suction pressure required, and a higher suction will in turn induce a greater soil heave plug. The m value, defined as the ratio of the volume of the soil heave plug to that of the penetrated caisson skirt wall, is adopted to evaluate the soil heave plug. The relationship between the m value and the undrained shear strength of the soil can be used to estimate the amount of soil heave plug and the caisson penetration for a concrete caisson with a wall thickness to external diameter ratio of 5% in normally consolidated clay conditions.